2016
DOI: 10.1111/febs.13813
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic cochaperone Sti1 is relevant for mitochondrial biogenesis and morphology

Abstract: Most mitochondrial proteins are synthesized in the cytosol prior to their import into the organelle. It is commonly accepted that cytosolic factors are required for delivering precursor proteins to the mitochondrial surface and for keeping newly synthesized proteins in an import-competent conformation. However, the identity of such factors and their defined contribution to the import process are mostly unknown. Using a presequence-containing model protein and a site-directed photo-crosslinking approach in yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 39 publications
2
52
0
1
Order By: Relevance
“…To investigate further the involvement of cytosolic factors in Fis1 biogenesis, the effect of deletion of the Hsp70 cochaperone Sti1 on mitochondrial levels of Fis1 was examined. Previously, we observed reduced Fis1 levels in whole cell lysate of sti1Δ cells . Analysis of mitochondria isolated from either sti1Δ or wild type (WT) cells revealed that at both normal (30°C) and elevated temperature (37°C) the levels of Fis1 are significantly reduced in the organelles from the mutated cells (Figure ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…To investigate further the involvement of cytosolic factors in Fis1 biogenesis, the effect of deletion of the Hsp70 cochaperone Sti1 on mitochondrial levels of Fis1 was examined. Previously, we observed reduced Fis1 levels in whole cell lysate of sti1Δ cells . Analysis of mitochondria isolated from either sti1Δ or wild type (WT) cells revealed that at both normal (30°C) and elevated temperature (37°C) the levels of Fis1 are significantly reduced in the organelles from the mutated cells (Figure ).…”
Section: Resultsmentioning
confidence: 80%
“…The wild‐type strains BY4741 and W303a/α were utilized. The sti1Δ strain was described before, ssa2‐4Δ + SSA1 wt and ssa2‐4Δ + SSA1 ts strains are a kind gift from Dr O. Pines, and the BY4741 pex19Δ strain was obtained from Euroscarf. The PEX19 gene in the W303a background was deleted by the homologous recombination approach .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, pathway 7). The cytosolic Hsp70, Hsp90, and their cochaperones participate in the stabilization and delivery of precursors onto the OMM for import . Interestingly, the ribosome‐associated chaperones, Ssb1, Ssb2 and Zuo1, were found to suppress ρ o ‐lethality and mPOS‐induced cell death in tim18 ∆, yme1 ∆, tom70 ∆, atp1 ∆ and aac2 A128P cells, and loss of these chaperones renders the cells ρ o ‐lethal .…”
Section: Conditions That Can Induce Mposmentioning
confidence: 99%
“…The site‐specific binding of Sti1 to the presequence of a mitochondrial precursor protein reported by Hoseini et al . adds a critical player into the early reactions that mediate protein targeting to mitochondria which will be instrumental to fill the black box in our understanding of this important process.…”
mentioning
confidence: 99%